Ecologically dynamic flywheel ergometer squat performance characteristics between national Olympic athletes with and without patellar tendinopathy - Choi, H.; You, J. S. H. (Isokinetics and Exercise Science, 2024)
BACKGROUND Patellar tendinopathy (PT) is a common injury involving inadequate eccentric (ECC) knee extensor contractions during dynamic sports activities. However, any discrepancies in ECC power output between Olympic athletes with and without PT utilizing a flywheel ergometer squat remain to be determined.